Incidence, risk factors, and outcomes of Panton-Valentine leukocidin-positive methicillin-susceptible staphylococcus aureus infections in Auckland, New Zealand - Muttaiyah, S.; Coombs, Geoffrey; Pandey, S.; Reed, P.; Ritchie, S.; Lennon, D.; Roberts, S. (American Society for Microbiology, 2010)
Panton-Valentine leukocidin (PVL) has been linked to invasive community-acquired methicillin-resistant Staphylococcus aureus infections. However, the association between disease and PVL-positive methicillin- susceptible Staphylococcus aureus (MSSA) has not been widely reported. We aimed to examine the epidemiology of PVL in clinical MSSA isolates from patients presenting to Auckland City Hospital. Four hundred eleven MSSA clinical isolates and 93 nasal carriage isolates were collected and tested for the presence of the lukSF-PV genes using PCR. The results were examined in light of host and disease factors. Multilocus sequence typing (MLST) was performed on a random subset of isolates to ensure that there was no single PVL-positive MSSA clone responsible for disease in Auckland. The prevalence of the lukSF-PV genes in MSSA isolates associated with disease (124/335; 37%) was not significantly different from the prevalence of the lukSF-PV genes in MSSA nasal carriage isolates (29/93; 31% [P = 0.33]). PVL-positive MSSA isolates in Auckland are genetically diverse and come from a number of different clonal complexes. PVL-positive infections peaked at between 10 and 20 years of age, with a subsequent decline. Pacific ethnicity, age, diagnosis of skin and soft tissue infection (SSTI), community-onset infection, and the need for surgical intervention were found by multivariate analysis to be independently associated with PVL-positive MSSA infection. More than one-third of MSSA infections in our patient population are caused by PVL-positive strains. Those patients with PVL-positive MSSA infection were more likely to be of Pacific ethnicity, be younger in age, have community-onset infection, have SSTI, and need surgical intervention. Copyright © 2010, American Society for Microbiology. All Rights Reserved.